Research on Strategies of Guiding Students to Imagine Performance in Dance Teaching of Secondary School - Huang, Wei (Journal of Theory and Practice of Contemporary Education, 2024)
Performance imagination plays an important role in dance education of secondary school, which directly affects students' dance performance ability. Therefore, training students' performance imagination ability in dance teaching of secondary school is of great significance for improving the effectiveness of dance education. Based on this, this paper mainly discusses the strategies of guiding students to perform imagination in dance teaching of secondary school.